magnum.fe: A micromagnetic finite-element simulation code based on FEniCS - Abert, Claas; Exl, Lukas; Bruckner, Florian; Drews, André; Suess, Dieter (Journal of magnetism and magnetic materials, 2013)
We have developed a finite-element micromagnetic simulation code based on the FEniCS package called magnum.fe. Here we describe the numerical methods that are applied as well as their implementation with FEniCS. We apply a transformation method for the solution of the demagnetization-field problem. A semi-implicit weak formulation is used for the integration of the Landau-Lifshitz-Gilbert equation. Numerical experiments show the validity of simulation results, magnum.fe is open source and well documented. The broad feature range of the FEniCS package makes magnum.fe a good choice for the implementation of novel micromagnetic finite-element algorithms.